Study of the Impact of Online Education on Student’s learning at University Level in Pakistan - Humaira Akhter (International Islamic University Islamabad, 2018)
The objective of this study was to explore the impact of online education and to analyze the online education on students' academic learning. The study helps both the students and teachers to know the impact of online education on students' learning. 300 students from Virtual University of twin cities of Pakistan were selected as a targeted population and 90 students selected as a sample size by using the simple random technique. The close-ended questionnaire was used for data collection. The link of online education with computer literacy, creativity among students, motivation of students towards learning, and performance of students was evaluated by the manual method. Results suggested that some major efforts must be made to continue to improve online technology that fosters dynamic learning opportunities for students through online education. It is recommended to have better distance learning environment or first-class online classrooms that can sense a learner's motivation level and respond adaptively.